Kewenangan Ayah Biologis Menjadi Wali Nikah Bagi Anak Hasil Zina Menurut Pandangan Imam Syafi’i dan Putusan Mahkamah Konstitusi (MK) NO. 16/PUU-VIII/2010 - Agung Sahbana Nasution; Sutrisna Sutrisna; Syarifah Gustiawati (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2022)
The presentence of marriage guardian is a must which should be considered. This research learn about Imam syafi'i viewpoint and Mahkamah Konstitusi Decision no 16-VIII-PUU/2010 about the authority of bioligical father to be marriage guardian for his out of marriage children.This purpose research is to analyst how Imam Syafii viewpoint and Mahkamah Konstitusi Decision about the authority of bioligical father to be marriage guatdian for his out of marriage children. This research is using yuridis normatif proccess with deskriptip kualitatif method. The result of this research is imam syafii gave 2 viewpoint about bioligical father to be marriage guardian for his out of marriage children. First, its allowed a father to be marriage guardian for his out of marriage children with provision the daughter born at least 6 month after her parents akad. Meanwhile, mahkamah konstitusi decision said "a child that was born out of marriage have a civil relation with her mother and mothers family and then a man as her father that could be prove by sains and technology or another evidence according to law has blood relation including civil relation with the father's family. ."this legal logic decision has consequence to out of marriage children descendants with her father. It is mean if we look at Mahkamah Decision a father could be a marriage guardian for out of children marriage without to see how old the womb that born after the marriage. Keyword: Guardian Authority, Child of Adultery, Imam Syafi’i and Constitutional Court Number 16/2010